Emergence of a New HIV Type 1 CRF01_AE Variant in Guangxi, Southern China - Zeng, Haiyan (Mary Ann Liebert, Inc., 2012)
The distribution of HIV-1 subtypes and genetic characterization of CRF01_AE in Guangxi, southern China were identified. The distribution of HIV-1 genotypes based on gag, pol, and partial env sequences (n=349) was as follows: CRF01_AE (66.5%), CRF08_BC (19.2%), CRF07_BC (7.2%), URF (4.6%), subtype B (1.7%), and subtype B′ (0.9%). CRF01_AE predominated in all geographic regions and risk populations and there were multiple introductions of CRF01_AE strains in Guangxi. We found a peculiar CRF01_AE monophyletic lineage distinct from other CRF01_AE viruses, and we designated it “CRF01_AE-v” for convenience. CRF01_AE-v circulating in both heterosexuals and injecting drug users (IDUs) had accounted for 39.7% of CRF01_AE. It showed a selective advantage in the Guangxi population and formed its own characteristic compared with all the CRF01_AE references. Our results suggested that CRF01_AE-v was a new variant of CRF01_AE and it might lead to a new epidemic in Guangxi.